2005
DOI: 10.1088/0957-0233/16/2/031
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic processing of DGA data produced by partial discharges for the prognosis of HV transformer behaviour

Abstract: One method for the identification of incipient transformer failures due to partial discharges involves measuring the concentration of dissolved gases in the transformer oil. The number of gases monitored is often considerable (⩾10), and there is a problem in tracking time varying patterns of the concentration of these gases to yield meaningful prognostic information. This contribution describes the use of chromatic processing techniques in the gas identification domain for yielding conveniently assimilable inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…In order to better optimize fatigue estimation, it is suggested that the physiological and physical indicators are treated separately in the chromatic domain pending the availability of additional test data to enable chromatic probability methods [11] to be invoked. Further tests are also needed to establish the extent to which swerve signals are discernible under other operating conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better optimize fatigue estimation, it is suggested that the physiological and physical indicators are treated separately in the chromatic domain pending the availability of additional test data to enable chromatic probability methods [11] to be invoked. Further tests are also needed to establish the extent to which swerve signals are discernible under other operating conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For the cases when physiological and physical indicators both contribute, it is anticipated that the tiredness scores from equations ( 5) and (7) would correlate to indicate similar rates of increase of tiredness and approaches to each of the two critical tiredness thresholds as given by equations ( 6) and (8). Otherwise the most critical indicator might be adopted pending further experimentation and the possible use of additional chromatically based prognosis as used by Zhang et al [11].…”
Section: Combination Of Physiological and Gyroscope Signalsmentioning
confidence: 99%
“…Currently, for PD diagnostics in power transformers, several measurement methods based on the different physical phenomenon are applied. These methods include: DGA [14][15][16], electrical method [17], ultra-high frequency (UHF) method [18][19][20][21] and AE method [8,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Also, its polar plots may be useful as an intermediate human interface to complex system behaviour. Chromatic processing can produce a qualitative characterisation of a system (behavioural trajectory) and additionally quantify this using, for example, secondary HLS analysis and deriving event probability measures (Zhang et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The polar plot representation is well suited for visualising and tracking system behaviour and for depicting the fusion of information about the monitored system from multiple sensors, using algorithms from colour science (Brazier et al , 2001a). Naturally, the patterns that are formed in HLS space to characterise system behaviour may also be quantified, for example, in terms of event probabilities (Zhang et al , 2005).…”
Section: Chromatic Processingmentioning
confidence: 99%